Novel Association of High C-Reactive Protein Levels and A69S at Risk Alleles in Wet Age-Related Macular Degeneration Women - Fernandez-Robredo, Patricia; Recalde, Sergio; Hernandez, Maria; Zarranz-Ventura, Javier; Molins, Blanca; Casaroli-Marano, Ricardo P.; Adan, Alfredo; Saenz-de-Viteri, Manuel; García-Layana, Alfredo (Frontiers in Immunology, 2018)
Purpose: To explore the relationship between plasma C-reactive protein (CRP) levels, the main ARMS2 gene Single Nucleotide Polymorphism (SNP) and gender in patients with neovascular Age related Macular Degeneration (wet AMD). Methods: Our study included 131 patients with wet AMD (AREDS category 4) and 153 control participants (AREDS category 1) from two Spanish retinal units. CRP levels were determined on blood samples by high sensitivity ELISA assay. According to their CRP level, subjects were categorized into three well-established CRP categories: low (<1.00 mg/L, L-CRP), moderate (1 to 2.99 mg/L, M-CRP) and high (>3.00 mg/L, H-CRP). Genomic DNA was extracted from oral swabs using QIAcube (Qiagen, Hilden, Germany) and the A69S; rs10490924 of ARMS2 gene was genotyped by allelic discrimination with validated TaqMan assays (Applied Biosystems, Foster City, USA). Univariate and multivariate logistic regression adjusted for age was used to analyze the genomic frequencies and to calculate odds ratio (OR) using SNPStats software. Results: Considering CRP risk categories, H-CRP group showed a significant [OR, 4.0; (1.9– 8.3)] association with wet AMD compared to L-CRP group. The risk genotypes of A69S (TT) SNPs showed anassociation with wet AMD risk [OR: 14.0, (4.8-40.8)]. Interestingly, the gender stratification of the CRP categories showed a significant increase in CRP levels in wetAMD women compared with control women [OR 6.9 (2.2-22.3)] and with wetAMD men [OR: 4.6, (1.3-16.9)]. In addition, the subgroup analysis of CRP within A69S genotype and gender showed a link in women between the A69S and CRP levels in the AMD group compared to controls [OR 4.2 (1.4-12.6)]. Conclusions: Our study shows, for the first time, that a different genetic association related to gender could contribute to AMD risk. As a consequence, the risk of female gender in the different CRP levels and A69S SNP frequencies could be taken into consideration to the established risk relationship of high levels of CRP and its association with risk A69S genotype.